Citrus monstruosa Discrimination among Several Citrus Species by Multivariate Analysis of Volatiles: A Metabolomic Approach. Issue 5 (3rd December 2015) - Petretto, Giacomo Luigi; Sarais, Giorgia; Maldini, Maria Teresa; Foddai, Marzia; Tirillini, Bruno; Rourke, Jonathan P.; Chessa, Mario; Pintore, Giorgio
Abstract: The origin and taxonomy of C itrus monstruosa (Rutaceae) are currently unknown and thus a nontargeted metabolomic analysis on the flavedo volatiles was performed. Headspace solid‐phase micro extraction coupled with gas chromatography analysis was applied to eight C itrus spp. including Citrus monstruosa, and the chemical composition of the volatile organic compounds (VOC) was analyzed to give a chemical comparison between different C itrus species. Forty‐four metabolites were detected across the species: several monoterpenes were found in all C itrus spp. and among them limonene comes first in all C itrus spp. ranging from 96.7 to 66.7%. Conversely, some molecules were found to be specific for only a few of the samples. The classical univariate evaluation of the VOC data is unlikely to give objective data for the cultivar classification; a multivariate approach, principal component analysis, is an easy to use, powerful tool. Therefore, a chemometric comparison between chromatographic data of all C itrus spp. was performed with the aim of understanding the role of VOC in the discrimination of the eight studied cultivars. Practical Application: A chemometrics' method was applied on the volatiles of eight C itrus spp. including C itrus monstruosa . Results were used to discriminate and classify C . monstruosa from several other C itrus spp. This method may also be used to discriminate other C itrus spp. as well as being applied to the volatiles‐based classification of other botanicals.